The two Lila Bennetts - Fenton, Liz; Steinke, Lisa (Lake Union Publishing, 2019)
When a fateful choice splits her life into two realities, Lila Bennett endures one existence as a vengeful kidnapper's hostage and another as a decorated criminal defense attorney who is targeted by a mysterious assailant.